The Effect of a Passing Training Program on Basketball Shooting Accuracy Among Students at SMPN 2 South Bengkulu - Farhan Ilham Apriyanto; Roni Syaputra; Desrio Windoro (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of passing drills on basketball shooting accuracy among students in the extracurricular basketball program at SMP Negeri 2 Bengkulu Selatan. The research method used was an experimental method with a pre-experimental design employing a one-group pretest-posttest design. The population for this study consisted of all 20 students in the basketball extracurricular program at SMP Negeri 2 Bengkulu Selatan. The research sample consisted of 15 students. The research instrument used a 5-point shooting test. The training program was conducted for 1 month and 2 weeks, with training sessions held 3 times a week, for a total of 15 sessions. Based on the results of the hypothesis test using the t-test, the calculated t-value of 11.215 was greater than the critical t-value of 2.145 (11.215 > 2.145). Thus, H₀ was rejected and H₁ was accepted. The results of the study indicate that there was a significant improvement of 90.63% in shooting accuracy among students in the extracurricular program at SMP Negeri 2 Bengkulu Selatan as a result of passing drills.